CFD analysis of photovoltaic panel performance under variable weather conditions with natural and forced convective cooling - Ayaz Aydin Abduljabbar; Manar Mohammed; Zahraa H. Mohammed Ali; Hussein Hayder Mohammed Ali; Furqan Haider Mohammed Ali; Timur Choban Khidir (International Journal of Renewable Energy Development, 2026)
The objective of this study is to numerically investigate the influence of climatic conditions, particularly ambient temperature and relative humidity, on the thermal and electrical performance of photovoltaic (PV) panels, and to evaluate the effectiveness of natural and forced convection cooling for both conventional and finned panel configurations. A multilevel computational fluid dynamics (CFD) model was developed using ANSYS Fluent 16.1 under realistic environmental conditions of Baghdad, Iraq. Two configurations were examined: a conventional flat panel and a modified panel equipped with longitudinal fins acting as a passive heat sink. Under both natural and forced convection, with an inlet air velocity of 1.5 m/s for forced cooling, the simulations took into account solar radiation, species transport to capture humidity effects, and the k–ω turbulence model. Under natural convection, the traditional panel attained a maximum surface temperature of 333.11 K with an electrical efficiency of 27.8%; forced convection lowered the temperature to 319.22 K and increased efficiency to 29.88% (7.5% improvement). Under natural cooling, the finned design lowered the temperature to 327.4 K, raising the efficiency to 28.66% (~3% increase). Under forced cooling, it further dropped to 315.5 K, reaching a maximum efficiency of 30.43%. This translates to advancements of 9.4% over the traditional natural cooling scenario and 6.17% over the finned natural cooling scenario. Yearly average results show that the finned design improves electrical efficiency by about 2% under natural convection and up to 6.53% under forced convection, whereas forced cooling of the conventional panel gives a 3.12% increase. The enhancement is primarily attributed to increased heat transfer surface area and improved convective mixing, particularly under natural convection where fin-induced vortices significantly enhance heat dissipation.